2015
DOI: 10.1186/s13029-015-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-docking study of malaria drug target enzyme transketolase in Plasmodium falciparum 3D7 portends the novel approach to its treatment

Abstract: BackgroundMalaria has been a major life threatening mosquito borne disease from long since. Unavailability of any effective vaccine and recent emergence of multi drug resistant strains of malaria pathogen Plasmodium falciparum continues to cause persistent deaths in the tropical and sub-tropical region. As a result, demands for new targets for more effective anti-malarial drugs are escalating. Transketolase is an enzyme of the pentose phosphate pathway; a novel pathway which is involved in energy generation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 69 publications
(60 reference statements)
2
27
0
Order By: Relevance
“…In the year 2013, the World Health Organization (WHO) estimated 198 million cases of malaria leading to 584,000 deaths worldwide [1]. The disease mostly prevails in the poor countries of tropical and sub-tropical regions of Sub-Saharan Africa, America and Asia [2]- [7]. The Plamodium species namely P. falciparum, P. vivax, P. malariae and P. ovale, and the lately reported species P. knowlesi are known to cause malaria [4] [5] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the year 2013, the World Health Organization (WHO) estimated 198 million cases of malaria leading to 584,000 deaths worldwide [1]. The disease mostly prevails in the poor countries of tropical and sub-tropical regions of Sub-Saharan Africa, America and Asia [2]- [7]. The Plamodium species namely P. falciparum, P. vivax, P. malariae and P. ovale, and the lately reported species P. knowlesi are known to cause malaria [4] [5] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Plamodium species namely P. falciparum, P. vivax, P. malariae and P. ovale, and the lately reported species P. knowlesi are known to cause malaria [4] [5] [8] [9]. Of the five species P. falciparum is the most responsible for causing the disease [2] [3] [5] [7].…”
Section: Introductionmentioning
confidence: 99%
“…The G1/S-specific cyclin-D1 protein sequence was downloaded from the UniProt database (P24385). 28 ProtParam 29 analysis showed that the protein has 295 amino acids. Its molecular weight is 33729.1 Da and its theoretical PI is 4.97.…”
Section: Resultsmentioning
confidence: 99%
“…This might be the result of several hydrogen bonding that was found such as Phe140, Glu166, Gln189, Asn142, and Pro168 at the active cavity of the main protease enzyme. Researcher suggests that non-covalent binding at the active site of the target protein may lead to possible inhibition and blockage of the protein (Hasan et al., 2015 ). On the other hand, the somatostatin analog, Vapreotide (VAP) was used to control tumor growth, progression, and metastasis.…”
Section: Discussionmentioning
confidence: 99%